Conditions for a meaningful writing retreat: Time, space, community and transition - Filippou Kalypso; Plamper Raakel (University of Borås, 2022)
This article investigates a five-day residential retreat for seven women from one academic institution and examines writing retreats through the analysis of texts written by the participants. The aims of this paper are 1) to develop more knowledge about the experiences of what constitutes good conditions for writing in a writing retreat context, and 2) to identify elements of a meaningful writing retreat. The experiences and reflections of the participants are examined and concludes to four conditions that shaped the meaningfulness of the retreat: transition, space, time, and community.